2023
DOI: 10.1186/s41927-023-00369-0
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the mitochondrial connection: development and validation of biomarkers for classifying and treating systemic lupus erythematosus through bioinformatics and machine learning

Haoguang Li,
Lu Zhou,
Wei Zhou
et al.

Abstract: Background Systemic lupus erythematosus (SLE) is a multifaceted autoimmune disease characterized by clinical and pathological diversity. Mitochondrial dysfunction has been identified as a critical pathogenetic factor in SLE. However, the specific molecular aspects and regulatory roles of this dysfunction in SLE are not fully understood. Our study aims to explore the molecular characteristics of mitochondria-related genes (MRGs) in SLE, with a focus on identifying reliable biomarkers for classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Two recent bioinformatics studies have suggested that Fam210b is an important candidate for the classification and therapeutic targeting of SLE [16,17]. To prove the role of Fam210b in SLE via experimental methods, we constructed mice with Fam210b knockout and found that Fam210b knockout leads to a low probability of lupus-like symptoms in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent bioinformatics studies have suggested that Fam210b is an important candidate for the classification and therapeutic targeting of SLE [16,17]. To prove the role of Fam210b in SLE via experimental methods, we constructed mice with Fam210b knockout and found that Fam210b knockout leads to a low probability of lupus-like symptoms in mice.…”
Section: Introductionmentioning
confidence: 99%